Ielts practice tests plus 3 - Matthews, Margaret (Longman, 2012)
IELTS practice tests plus provides practice in all four modules of the IELTS examination: Listening, Reading, Writing and Speaking. It includes five complete practice tests incorporating the 2001 modifications to the Speaking module, additional Reading and Writing modules for General Training candidates, plus a full description of the exam, students' top questions answered, and 'skills for IELTS' sections training key subskills for each module.